Pengembangan Aplikasi Penyewaan Lapangan Badminton Berbasis Android - Ade Lia Saputri; Sutarman Sutarman (Journal of Information System Research (JOSH), 2025)
This mobile application to simplify the process of renting badminton courts at GOR Biru Sport Center Yogyakarta, addressing the inefficiencies of the manual system that had been used until now. Using a Design Thinking approach, we identified user issues through interviews and observations, then designed a Flutter-based prototype featuring key functionalities: real-time court availability updates, integrated digital payments (QRIS and e-wallet), and an admin dashboard for schedule management. Testing results showed significant improvements, evidenced by reduced booking time, 98% accuracy in court availability information, and the elimination of physical queues. The app received a usability score of 4.6/5 from users, proving its effectiveness in enhancing customer experience while improving field management efficiency. This digital solution not only addresses current issues but also opens opportunities for further feature development, such as membership programs and calendar integration. This research serves as tangible evidence of how mobile technology can transform conventional systems in sports facilities.